ANALISIS FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN BADAN LAYANAN UMUM DAERAH (BLUD) PUSKESMAS BOYOLALI I - Ardiningsih, Wahyu Juwita; Sriyanto (Jurnal Akuntansi dan Pajak, 2024)
Finding out how organizational culture, human resource competency, and the local government's accounting system affect Puskesmas Boyolali I's financial report quality is the primary goal of this study. To ascertain the interplay of the investigated variables, the study employs a causal quantitative approach. A validity and reliability test has been conducted on the questionnaire that is used to gather data. This study employed census sampling to choose a representative sample of all employees from a population of 38. Using SPSS 2.6, we tested hypotheses and ran multiple linear regressions on the collected data. Results from the study and discussion indicate that organizational culture, human resource competency, and the local government accounting system all contribute to Puskesmas Boyolali I's high-quality financial reports. Keywords : competence, local government accounting system, organizational culture, quality of financial reports